1999
DOI: 10.1161/01.cir.99.15.2041
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Extracellular and Intracellular Adenosine Production

Abstract: Background-Inhibitors of adenosine membrane transport cause vasodilation and enhance the plasma adenosine concentration. However, it is unclear why the plasma adenosine concentration rises rather than falls when membrane transport is inhibited. We tested the hypothesis that the cytosolic adenosine concentration exceeds the interstitial concentration under well-oxygenated conditions. Methods and Results-In isolated, isovolumically working guinea pig hearts (nϭ50), the release rate of adenosine and accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 27 publications
7
94
0
Order By: Relevance
“…However, it is not clear whether the source of adenosine is intracellular or extracellular under stress conditions. Deussen et al (9) showed that, in guinea pig hearts under well-oxygenated conditions, addition of NBMPR increased interstitial adenosine concentrations and the source of adenosine was extracellular.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether the source of adenosine is intracellular or extracellular under stress conditions. Deussen et al (9) showed that, in guinea pig hearts under well-oxygenated conditions, addition of NBMPR increased interstitial adenosine concentrations and the source of adenosine was extracellular.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Dipyridamole inhibits this facilitated diffusion in humans in vivo and thereby increases extracellular adenosine concentration, which subsequently activates adenosine receptors at sites of adenosine formation. 13,14,24 -26 These observations justify the use of dipyridamole-induced vasodilation as a read-out of extracellular adenosine formation.…”
Section: Rosuvastatin Increases Dipyridamole-induced Vasodilationmentioning
confidence: 99%
“…Figure 1A illustrates that a physiological concentration of adenosine (1 nmol/L) [17,18] decreased I h from 16.1±0.3 pA (I h (Con) ) to 9.9±0.7 pA (I h (Ado) ) by 39% (n=8, P<0.05, upper panel). The decrease in I p was not due to pump "rundown" because the adenosine effect was reversible upon washout (lower panel of Figure 1A).…”
Section: Resultsmentioning
confidence: 99%